THE MUQAWAMA (RESISTANCE): THE CASE OF HAMAS (Journal of the Spanish Institute for Strategic Studies, 2018)
The view of Hamas as an insurgent movement seeking the destruction ofIsrael and the construction of an Islamic State on historical Palestinianterritory is based on its own doctrine, known as the “muqawama” orresistance doctrine. The “muqawama doctrine” has its own distinctiveelements and is independent of classical insurgency frameworks; hence,these new elements constitute a valuable analytical tool for the study ofemerging insurgent and Islamist phenomena.